Prática do dizer, prática do fazer: cineclubismo, imagens e política - Silva, Francine Nunes da (2011)
This thesis is a starting point to contact ethnographic film clubs developed with the lantern Cineclube Aurelius in the town of Santa Maria RS Brazil cinema clubs linked to the movement. And extension of research work, begun between 2006 and 2007, which resulted in the graduation dissertation in Social Sciences at the Universidade Federal de Santa Maria, entitled "Cineclube Lanterninha Aurélio. An ethnographic study on film clubs and sociability in Santa Maria". It was a study in order to examine ways of practice, discourse and organization of film clubs in its temporal dimension, political and cultural. Thus, the theme of the film club and emerges as a sum by way of diverse elements - words, images, memories, art - that give meaning to the experience and context.